Motif Jepang Menandatangani Perjanjian Akses Timbal Balik Jepang – Australia - Cahyandari, Eka (Jurnal Politica, 2024)
This research aims to analyze Japan's motives for signing the Reciprocal Access Agreement(RAA) with Australia. Using qualitative descriptive method and secondary data collectionfrom literature studies, the analysis is based on Stephen M. Walt's Balance of Threat theory.The study reveals that Japan's decision to enter the RAA is influenced by the perceived threatfrom China, encompassing four critical aspects. Firstly, China’s superior military, economic,and population strength compared to Japan. Secondly, the geographical proximity, withthe closest distance between Japan and China being 603 km. Thirdly, China’s offensivecapabilities, highlighted by its development and test launches of hypersonic missiles. Lastly,the aggressive intentions perceived by Japan, viewing China as a potential threat to securityand peace in the Indo-Pacific region. In response to these threats, Japan has chosen to balancewith Australia, influenced by three main factors. Firstly, Japan's relatively stronger militarycapabilities compared to Australia. Secondly, the strategic alignment and availability of allies,with Japan recognizing shared interests with Australia. Thirdly, the current period of peace,despite the looming threats, has prompted Japan to solidify its security posture through theRAA with Australia. This strategic alliance is seen as a measure to enhance Japan’s securityand stability in the face of potential Chinese aggression.